Research on instability characteristics and control technology of the mining roadway below the remaining coal pillars in the goaf - CAO Jinzhong; GAO Le; YAN Pengfei; LI Meng; CHEN Lei; YANG Huakang (Gong-kuang zidonghua, 2022)
When the extra thick coal seam is mined in the goaf, the remaining coal pillar of upper coal seam and adjacent working face will have an important impact on the stability of mining roadway. At present, the research on deformation and failure mechanism and control of mining roadway does not consider the complex environment of gob-side roadway in extra thick coal seam under the condition of short distance coal pillar mining. In order to solve the problem, taking the 30503 repaired roadway in Tashan Coal Mine as the engineering background, the deformation and failure mechanism of the roadway is analyzed by using the methods of field monitoring, theoretical analysis and numerical simulation. And the corresponding surrounding rock support technology is proposed. A roof separator is arranged on the roof of 30503 repaired roadway to monitor and record the rock displacement at each position of the roof in real time. The monitoring results show that the surrounding rock in the roof of 30503 repaired roadway has been broken due to the impact of adjacent working face and the short distance to the overlying remaining coal pillar. After the roadway excavation, the roof deformation speed is fast, the seperation volume increases continuously and the impact range is wide. According to the monitoring results, the impact of the remaining coal pillar on the deformation and failure of the roadway and the impact of the fracture position of the basic roof on the deformation and failure of the roadway are analyzed. The results show the following points. ① The unreasonable arrangement of the roadway is an important reason for the damage of the repaired roadway. At the same time, in order to avoid the impact of the remaining coal pillar, the roadway is arranged at a distance of more than 35 m from the center of the coal pillar (25 m from the edge of the coal pillar). ② The excavation position of repaired roadway is seriously affected by the remaining coal pillar, and the roadway is in the high stress concentration area before excavation. When the adjacent 30501 working face is mined, the basic roof breaking position is located above the roof of the repaired roadway, which is the direct cause of the broken roof of the roadway. According to the above analysis results, the numerical simulation analysis is carried out on the evolution law of deviatoric stress distribution of coal pillars with different widths, and the targeted technical scheme of surrounding rock stability control is proposed. ① On the premise of ensuring sufficient safety of the coal pillar and avoiding waste of resources, the width of the coal pillar in the 30503 repaired roadway section is set to 8 m. ② When excavating the gob-side roadway in the short distance extra thick coal seam, hydraulic fracturing measures are adopted to reduce the impact of the overlying coal pillars on the coal seam. ③ The support scheme of bolt-mesh-anchor+guniting+single pillar is selected to support the newly excavated roadway. In order to verify the application effect of the surrounding rock stability control technology, the cross observation method is used to continuously monitor the roadway deformation during the excavation of the new repaired roadway in 30503 working face. The results show that the deformation of the two sides is 90 mm, the deformation of the roof and floor is 331 mm, and the deformation of the surrounding rock is effectively controlled.